An efficient geo–aware peer–to–peer resource discovery and sharing scheme in vehicular ad–hoc networks. (2nd January 2014) - Dow, Chyi–Ren; Lin, Pei–Jung; Lee, Yu–Hong; Lin, Ya–Chen; Hwang, Shiow–Fen
There has been a recent increase in research on vehicular ad–hoc network (VANET) technology. Peer–to–peer (P2P) systems have also been widely used for resource sharing. This paper proposes an efficient geo–aware P2P search mechanism to enable resource discovery and sharing on VANETs. The proposed discovery and sharing schemes are based on virtual backbone architecture. The schemes limit the data–exchanging region to reduce unnecessary message transmissions. They establish coordinators to store information and manage local resource information. If more vehicles own the resources, the user has more opportunities to discover and obtain the resources. Three piece selection mechanisms, nearest–first, rarest–first and in–order, are proposed to download resource pieces from other vehicles and to improve the dissemination efficiency speed at which resources piece to networks. Experimental results demonstrate that the searching and sharing schemes are efficient and outperform other schemes in terms of satisfactory ratio and download time.